The economics of choice, change, and organization : essays in memory of Richard M. Cyert - March, James G.; Augier, Mie; Cyert, Richard Michael (Cheltenham, UK ; Northhampton, MA : E. Elgar, 2002)
This collection of essays was commissioned for this volume in honour of the ideas and work of the late Richard M. Cyert who made a seminal contribution to the fields of industrial organization and change. In keeping with the range and significance of his work, the essays in this volume examine the economics of decision making, uncertainty, information processing, learning, evolution and organizational structure. Topics covered include: behavioural and evolutionary theories of the firm; cognitive factors in organization and economic action; the place of rules in organizations; learning from experience and from the knowledge of others; selection in economic change; and the impact of information technology and the evolution of organizational forms. The collection emphasizes the adaptive nature of economic action and the links between economies and studies of human information processing and action. It should be interesting reading for scholars with an interest in behavioural and adaptive economics, along with industrial organization.
Includes bibliographical references and index.
oif 15/07/14
Loans
Keywords: Industrial organization (Economic theory); Organizational learning; Organizational behavior; Economics - organization